Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2147/ijn.s357598
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine: An Emerging Novel Therapeutic Strategy for Hemorrhagic Stroke

Abstract: Hemorrhagic stroke is one of the most devastating diseases worldwide due to a high rate of disability and mortality with few effective treatments. Recent advances in nanomedicines to promote hemostasis, drug delivery, neuroprotection, and nerve regeneration may provide insight into hemorrhagic stroke treatment. In this review, we first view the pathophysiology and conventional therapeutics of hemorrhagic stroke. Second, we comprehensively summarize the current nanomedicines applied in hemorrhagic stroke, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 116 publications
0
22
0
Order By: Relevance
“…Recently, exosomes have been reported to have great potential in treating SAH. [32] Exosomes have been shown to carry miRNAs, and exosomal miRNAs play important roles in disease development. [33] Previous protective effect against EBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, exosomes have been reported to have great potential in treating SAH. [32] Exosomes have been shown to carry miRNAs, and exosomal miRNAs play important roles in disease development. [33] Previous protective effect against EBI.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, exosomes have been reported to have great potential in treating SAH. [ 32 ] Exosomes have been shown to carry miRNAs, and exosomal miRNAs play important roles in disease development. [ 33 ] Previous studies have shown that systemic exosomal miR‐193b‐3p can attenuate BBB damage and neuroinflammation, thereby exhibiting a protective effect against EBI.…”
Section: Discussionmentioning
confidence: 99%
“…The NPs can wrap around hydrophilic and hydrophobic drugs to increase their solubility and stability. More so, some of the inorganic or polymeric NPs developed can scavenge ROS and sequester iron thus offering a potential approach for mitigating iron overload-induced injuries and oxidative stress (Xu et al, 2022). Furthermore, nanomedicine has shown promise in modulating apoptotic pathways, both intrinsic and extrinsic and reducing the burden of Aβ-peptides, a critical initiator of AD.…”
Section: Nanoparticles In Neurodegenerative Diseasementioning
confidence: 99%
“…[21,43] As described by R. Ellis-Behnke, [18b] these hemostatic medical devices did favor the integrating development of multiple surgical techniques in different aspects and achieved the desired intraoperative hemostatic performance and safe post-operative outcome in various subspecialized surgical procedures. [13,21] Due to extensive basic research in injectable scaffolding matrix, [44] regenerative medicine, [106] 3D cell culture, [107] and drug delivery nanocarrier, [43] which convincingly pave the way for rapid translation to clinically medical application, RADA16 peptide hydrogel is not only a member of bioengineering peptide hydrogel biomaterial and but also represents one category of emerging hemostatic devices for the effective management of traumatic or surgical bleeding, including non-compressible torso hemorrhage, [7] persistent bleeding in the oozing raw surface, [108] intracranial or intraspinal hemorrhage, [109] and wound tissue closure. [70] Compared with natural-derived polysaccharides, polymers, and protein materials, [110] RADA16 nano-hemostat solution exhibited multiple well-recognized advantages malleable to intracorporal use in surgical settings, such as wound shape compliance, tunable stiffness, reliable biocompatibility, safe degradability, flexible usability, facile wound healing, instant blood clotting capability, and rapid functionalization, [13,51] which are not accessible to current traditional hemostatic materials.…”
Section: Nano-hemostat Solution For Surgical Usementioning
confidence: 99%